Environmental management accounting in Malaysian local government: a case of solid waste management - Abdullatiff, Nik Kamaruzaman; Hasan Ashari, Anis Abul; Ahmad, Junaidah Hanim; Wan Ahmad, Wan Noraswaniaty; Mustafa @ Busu, Zanirah (Universiti Teknologi MARA, Kelantan, 2018)
Local governments in Malaysia, have faced an emerging challenge of the growing quantity of solid waste generation and the unorganized management of space waste disposal in recent years. Indeed, the solid waste management is actually “a wake-up call” to many local government administrations – to understand and managing environment. The federal government has urged and demonstrated the importance of developing strategies to make full environmental costs and impacts of solid waste disposal (economically as well as environmentally) accountable for waste management decision making. However, research into this field is limited in our country, especially related to management accounting. This paper investigates the development of environmental management accounting practices in local government in relation to solid waste management. Specifically, the paper discusses the solid waste disposal costs and the potential economic values of solid waste. Using literature search as research design, this paper applies the analysis using theoretical framework of symbolic-interactions where the understandings of the world are derived from social interaction and modified through interpretation. Minimal biased methods were used for acquiring literature for the paper. A number of databases in fields such as sociology, social sciences, psychology, and economics were used to acquire literature on the topic. It is expected from this research resulting to derive the complementary explanations for the development of environmental management accounting in solid waste – combining the social system-based theories normally used in environmental studies and the contextual dynamics based on contingency theory of management accounting in effort to explain environmental changes in local government.